Training Does Not Alter Muscle Ceramide and Diacylglycerol in Offsprings of Type 2 Diabetic Patients Despite Improved Insulin Sensitivity. (29th September 2016) - Søgaard, Ditte; Østergård, Torben; Blachnio-Zabielska, Agnieszka U.; Baranowski, Marcin; Vigelsø, Andreas Hansen; Andersen, Jesper Løvind; Dela, Flemming; Helge, Jørn Wulff
Abstract : Ceramide and diacylglycerol (DAG) may be involved in the early phase of insulin resistance but data are inconsistent in man. We evaluated if an increase in insulin sensitivity after endurance training was accompanied by changes in these lipids in skeletal muscle. Nineteen first-degree type 2 diabetes Offsprings (Offsprings) (age:33.1 ± 1.4  yrs; BMI:26.4 ± 0.4  kg/m 2 ) and sixteen matched Controls (age:31.3 ± 1.5  yrs; BMI:25.3 ± 0.7  kg/m 2 ) performed 10 weeks of endurance training three times a week at 70% of VO2 max on a bicycle ergometer. Before and after the intervention a hyperinsulinemic-euglycemic clamp and VO2 max test were performed and muscle biopsies obtained. Insulin sensitivity was significantly lower in Offsprings compared to control subjects (p < 0.01 ) but improved in both groups after 10 weeks of endurance training (Off:17 ± 6 %; Con:12 ± 9 %, p < 0.01 ). The content of muscle ceramide, DAG, and their subspecies were similar between groups and did not change in response to the endurance training except for an overall reduction in C22:0-Cer (p < 0.05 ). Finally, the intervention induced an increase in AKT protein expression (Off:27 ± 11 %; Con:20 ± 24 %, p < 0.05 ). This study showed no relation between insulin sensitivity and ceramide or DAG content suggesting that ceramide and DAG are not major players in the early phase of insulin resistance in human muscle.